Febrile convulsions in a national cohort followed up from birth. II–Medical history and intellectual ability at 5 years of age. Issue 6478 (4th May 1985) - Verity, C M; Butler, N R; Golding, J
Abstract : Three hundred and three children with febrile convulsions were identified in a national birth cohort of 13 135 children followed up from birth to the age of 5 years. Breech delivery (p less than 0.05) was the only significantly associated prenatal or perinatal factor. There were no associations with socioeconomic factors. Excluding the 13 known to be neurologically abnormal before their first febrile convulsion, children who had had a febrile convulsion did not differ at age 5 from their peers who had not had febrile convulsions in their behaviour, height, head circumference, or performance in simple intellectual tests.